Crítica ao capitalismo desenvolvimentista : Belo Monte, impactos e etnocídios - Monteiro, Dion Márcio Carvaló, 1968- (2023)
Orientadores: Marilda Aparecida de Menezes, Mauro William Barbosa de Almeida